THE TRADITION OF SENDING OFF TO MILITARY IN CULTURAL MEMORY: EXAMPLE OF BASKIL (ELAZIĞ) AND ITS SURROUNDINGS - Şenocak, Ebru (TÜRKİYE TEMEL BİLİMLER ARAŞTIRMA VAKFI, 2020)
Baskil is one of the important districts of Elazığ where cultural values are kept alive. The people's protecting their traditional values ensured that the culture of the region remained alive for many years. Yahya Kemal says that "I am neither ruined nor reveller / I am the future whose root is in the past.” This deep-rooted commitment to ancestor cult, history and cultural values is highly important for raising individuals who are aware of their identity. Tradition is the continuity of cultural values, which are accepted as sacred in a society, by being transferred from generation to generation. Each individual creates immortal codes in collective consciousness with the values s/he carries from the social heritage of the nation to which s/he belongs. Going into the army is also a divine national service and is blessed with traditional values among the people. Military service is an important transition period that creates change and transformation in the life of every young person who leaves the family home. Among the people, not giving a girl in marriage to the young man who has notperformed his military service, indicates the importance of military service as a place of passage to adulthood. In the study, rituals (throwing the young man up three times, to make him bite a bagel, baking eggs in the soldier’s letters and make him eat, etc.) related to the tradition of sending off to military in Baskil and its surroundings have been handled in terms of their importance in cultural memory and have been analyzed symbolically. Thus, the importance of mythology and beliefs in the formation of traditions has been emphasized.

Baskil, kültürel değerlerin canlı bir şekilde yaşatıldığı Elazığ’ın önemli ilçelerinden birisidir. Halkın geleneksel değerlerine sahip çıkması, bölge kültürünün uzun yıllar canlı kalmasını sağlamıştır. Yahya Kemâl “Ne harâbî ne harâbâtîyim / Kökü mazide olan âtîyim.” diyor. Ata kültüne, tarihe ve kültürel değerlere olan bu köklü bağlılık, kimlik bilincine sahip bireyler yetiştirme açısından oldukça önemlidir. Gelenek, bir toplumda kutsal kabul edilen kültürel değerlerin, nesilden nesile aktarılarak süreklilik arz etmesidir. Her birey, ait olduğu milletin toplumsal mirasından taşıdığı değerlerle kolektif bilinçte ölümsüz kodlar oluşturur. Askere gitme de kutsal bir vatan görevi olup halk arasında geleneksel değerler ile kutsanmaktadır. Askerlik, baba ocağından ayrılan her gencin hayatında, değişim ve dönüşüm yaratan, bilinç oluşturma açısından önemli bir geçiş dönemidir. Halk arasında askere gitmeyen gence kız verilmemesi, askerliğin erginlenme mekânı olarak önemine işaret etmektedir. Çalışmada, Baskil ve çevresinde askere yollama geleneğine bağlı ritüeller (genci üç defa yukarı fırlatma, simit ısırtma, askerin mektuplarında yumurta pişirip ona yedirme vb.) kültürel bellekteki önemi açısından ele alınarak sembolik olarak tahlil edilmiştir. Böylece geleneklerin oluşumunda mitolojinin ve inanışların önemi vurgulanmıştır.
KÜLTÜREL BELLEKTE ASKERE YOLLAMA GELENEĞİ: BASKİL (ELAZIĞ) VE ÇEVRESİ ÖRNEĞİ
Keywords: Cultural Studies; Kültürel çalışmalar; Creative Arts and Writing; Sanat ve Edebiyat